Studies on protein profile of Ascardia galli and its host Gallus gallus domesticus - Bhure, D B; Nima, Kadam; Nanware, S S; Garad, V B (International Multidisciplinary Research Journal, 2012)
The present investigation deals with the protein content in nematode parasite Ascardia galli and its host tissue i.e. normal and infected intestinal tissue of Gallus gallus domesticus. The result obtained an amount of protein content in the present study indicates that the amount of proteins present in nematode parasites is low as compared to protein present in infected intestine as well as in normal intestine.